DEVELOPMENT OF SIGIL-BASED ADDITIVES AND ADDICTIVE SUBSTANCES TEACHING CHART FOR JUNIOR HIGH SCHOOL STUDENTS: ALTERNATIVE LEARNING RESOURCES DURING A PANDEMIC - Nor Imamah; Laily Yunita Susanti (INSECTA: Integrative Science Education and Teaching Activity Journal, 2021)
Research and development of sigil-based teaching materials based on facts in yhe field, namely students rarely read textbooks in printed form because the display is less attractive, additive and addictive substances have not been delivered as a whole so thaht astudents miss lessons and lack insight. When in class students tend not to play attention because the learning used by teachers is often convensional and rarely uses media. Teaching materials are needed by students in learning activities that can be used anytime and anywhere so that learning activities can be efficient. The purpose of the study was to describe the results of validation and student responses to sigil-based teaching materials for junior high schools. This type of research is the research and development of R&D (Research and development). The development model in this study uses a model developed by Thiagarajan 4-D. The product that has been developed is then validated by 2 (two) lecturers from the Faculty of Tarbiyah and teacher Training consisting of material experts and media experts as well as one science teacher of SMP Plus Darus Shlolah as user expert. After being validated, the product is then field tested to determine student responses. The results of the materials expert assessment are 98.75%, 91.42% media expert and 92.30% user expert, all three have a high percentage so that the developed digital teaching material has the criteria of “very valid”. The small-scale trial results showed a percentage of 78.4% so they included the criteria of “interesting”. Large-scale trial results the percentage of results is 83.3% so it includes the criteria of “very interesting”.